(untitled) (Journal of Dhaka Medical College, 2021)
Introduction: Osteoarthritis (OA) is the most prevalent chronic joint disorder worldwide and is associated with significant pain and disability. The introduction of 25% Dextrose injection has been viewed as an advance in the management of OA knee. Methods: A prospective, randomized clinical trial was conducted with 84 cases in the Physical Medicine and Rehabilitation (PMR) department of BSMMU. Group A, 42 patients received single dose 25% Dextrose injection intra articular 8ml, exercise and ADL; Group B, 42 patients received exercise and ADL. Outcomes were measured by OA specific translated and validated Bengali instrument- Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) questionnaire and visual analogue scale (VAS 0-10). They were followed up for 6 months. Result: At the initial stage and in week 4, there was no statistical difference between two groups regarding VAS score (as p value was >0.05). But in week 12 and 24, there was highly significant statistical difference regarding VAS score between two groups as the p value was <0.001. Again at the initial stage and week 4, there was no statistical difference between two groups regarding stiffness and physical function score. But in week 12 and 24, there was significant statistical difference regarding stiffness and physical function score between two groups as the p value was less than 0.05. Conclusion: Intra-articular injection of 25% dextrose administered to patients with OA knee has significant effects in pain reduction and functional improvement. J Dhaka Medical College, Vol. 29, No.2, October, 2020, Page 138-144